Sensitivity of seismic measurements to frequency‐dependent attenuation and upper mantle structure: An initial approach. Issue 7 (1st July 2014) - Bellis, C.; Holtzman, B.
Abstract This study addresses the sensitivity of seismic attenuation measurements to dissipative mechanisms and structure in the Earth's upper mantle. The Andrade anelastic model fits experimental attenuation data with a mild power law frequency dependence and can be scaled from laboratory to Earth conditions. We incorporate this anelastic model into 400km 1‐D thermal profiles of the upper mantle. These continuous‐spectrum models are approximated by multiple relaxation mechanisms that are implemented within a finite‐difference scheme to perform wave propagation simulations in 1‐D domains. In two sets of numerical experiments, we evaluate the measurable signature of the intrinsic attenuation structure. The two sets are defined by thermal profiles with added step functions of temperature, varying in (i) amplitude and depth or (ii) amplitude and sharpness. The corresponding synthetic data are processed using both the conventional t* approach, i.e., a linear regression of the displacement frequency spectrum, and an alternative nonlinear fit to identify the integrated value of attenuation and its frequency dependence. The measured sensitivity patterns are analyzed to assess the effects of the anelastic model and its spatial distribution on seismic data (in the absence of scattering effects). We have two straightforward results: (1) the frequency dependence power law is recoverable from the measurements; (2) t* is sensitive to both the depth and the amplitude of the step, and it is insensitive to the sharpness of the step, in the 0.25 to 2 Hz band. There is much potential for gaining information about the upper mantle thermodynamic state from careful interpretation of attenuation.